Constructed sociabilities: the social use of architecture in ‘Bracara Augusta’ - Machado, Diego; Magalhães, Fernanda (Romanitas - Revista de Estudos Grecolatinos, 2023)
The knowledge about Bracara Augusta has been made possible, to a large extent, by the development of systematic archaeological activities in recent decades. Indeed, the valorisation of archaeological data from excavations carried out in provincial cities has allowed the widening of studies on the Roman world beyond the spatial limits that textual documentation provides. In this sense, we will seek to analyse the ways in which the most prominent habitants of the city acted through the materiality constructed and consumed by these groups, as an indication of the way that the elites sought to assert and maintain their statuses before their peers and the other inhabitants of the conuentus bracaraugustanus.
Keywords: Urbanism; Architecture; Society; Performance; Bracara Augusta